Profitability in microfinance institutions in Peru 2018-2019 - León Reyes, Víctor Manuel (2022)
This article aims to analyze the factors that influence the profitability of rural saving and credit banks and municipal saving and credit banks in Perú, therefore it analyzes the factors related to the internal management of each institution. Portfolio of default and operating expenses are considered as variables that influence in its profitability. The research has a quantitative approach and the data has been structured in the form of panel data with fixed effects; the use of the panel data methodology allows us to determine the existence of a causal relationship between the variables analyzed. Finally, the results indicate that the explanatory variables show high significance, both at the general level of the model and at the individual level.